THE EFFECTS OF POVERTY ON THE HUMAN PSYCHE REFLECTED IN RUPERT BROOKE’S LITHUANIA: A PSYCHOANALYTIC STUDY - Sumarsono, Irwan (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2023)
This study analyzes the psychological effects of poverty on individuals using Rupert Brooke's play,